PENGEMBANGAN APLIKASI (GSM) BERBASIS ANDROID DALAM PEMAHAMAN MASASE OLAHRAGA DAN PENCEGAHAN CEDERA BAGI GURU PJOK - Ardiansyah, Moh Wahyu; Wahjuni, Endang Sri; Roepajadi, Joesoef (Universitas Negeri Surabaya, 2022)
Knowledge related to the process of providing first aid and early injury prevention during PJOK learning activities (sports) is an important thing that needs to be known. Therefore, this study aims to analyze the GSM application model and analyze the feasibility of an Android-based GSM application in understanding sports massage and injury prevention for PJOK teachers. Data collection techniques in this study used product validation sheets and questionnaires. The data analysis technique in this study used qualitative data analyzed by descriptive statistics. The subjects of this study were PJOK teachers throughout Surabaya who were divided into small groups of 15 people and large groups of 35 people. The results of the small group trial include 3 aspects of the assessment in the form of aspects of appearance, aspects of content/material, aspects of usefulness. The display aspect with a total score of 20 is in the “Good Enough” category, the content/material aspect with a total score of 38.6 is in the “Good enough” category, and the usefulness aspect with a total score of 15.3 is in the “Good” category. The results of the large group trial of the display aspect with a total score of 24 including the